2016
DOI: 10.1080/19420862.2016.1225643
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies against pools of mono- and polyacetylated peptides selectively recognize acetylated lysines within the context of the original antigen

Abstract: Post-translational modifications (PTMs) strongly influence the structure and function of proteins. Lysine side chain acetylation is one of the most widespread PTMs, and it plays a major role in several physiological and pathological mechanisms. Protein acetylation may be detected by mass spectrometry (MS), but the use of monoclonal antibodies (mAbs) is a useful and cheaper option. Here, we explored the feasibility of generating mAbs against single or multiple acetylations within the context of a specific seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…For Aib-Enkephalin, we observed an increase from 51% to about 74% and a remarkable increase of yield in the Aib-Aib coupling. Also in the Aβ [26][27][28][29][30][31][32][33][34][35] , which are both predicted to be hot spots of aggregation-prone regions. These sequences contain residues found missing in the most abundant deletion side products (see mass spectra of Figures 4A and 5A and Table S1) that are then mostly suppressed in the synthesis performed under the conditions of protocol II (see mass spectra of Figures 4B and 5B and Table S1).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For Aib-Enkephalin, we observed an increase from 51% to about 74% and a remarkable increase of yield in the Aib-Aib coupling. Also in the Aβ [26][27][28][29][30][31][32][33][34][35] , which are both predicted to be hot spots of aggregation-prone regions. These sequences contain residues found missing in the most abundant deletion side products (see mass spectra of Figures 4A and 5A and Table S1) that are then mostly suppressed in the synthesis performed under the conditions of protocol II (see mass spectra of Figures 4B and 5B and Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…As a fragment of the prototypical aggregating polypeptide Aβ , Aβ [26][27][28][29][30][31][32][33][34][35] has also strongly aggregating properties [18,31,32]. The AGGRESCAN prediction for this peptide (Figure S2, dotted line) suggested that region 29 AIIGL 33 exhibits a very high aggregation tendency.…”
Section: Aβ[26-35] Fragment Synthesismentioning
confidence: 99%
See 3 more Smart Citations